Petrogenetic implications for the Merensky Reef: a platinum-group element distribution study from wide-reef facies in the western Bushveld Complex, RSA - Largatzis, Savvas Anthony (Rhodes University, Faculty of Science, Department of Geology, 2016)
Despite decades of research and its economic importance, the formation of the Merensky Reef still remains controversial. This study reports on the distribution of platinum-group elements within widereef facies in an attempt to identify petrogenetic controls in the formation of the Merensky Reef. Widereef Merensky was sampled from Eland Platinum Mines in the western Bushveld. Macroscopic investigation of the drillcore identified a basal chromitite stringer overlying an anorthositic footwall. The reef comprised a pyroxenite unit while the hangingwall comprised noritic, leuconoritic and anorthositic units (upwards the stratigraphy). Furthermore, an anorthositic seam was identified within the pyroxenite reef, near the top of the unit. Ophitic textures of orthopyroxene oikocrysts comprising inclusions of plagioclase chadacrysts suggest that the crystallization of plagioclase preceded the crystallization of orthopyroxene. Furthermore, plagioclase and orthopyroxene were shown to be in mineral disequilibrium with one another. Pervasive hydrous alteration features throughout the Merensky Reef suggest late stage deuteric alteration. Mineral chemistry of plagioclase cores recorded ranges for An content in the Merensky Reef as follows: An72-79 in the anorthositic footwall, An71-77 in the chromitite stringer, An45-78 in the pyroxenite reef unit, An47-73 in the anorthosite reef unit, An72-76 in the norite hangingwall, An75-77 in the leuconorite hangingwall and An72-77 in the anorthosite hangingwall. This suggest that the reef units were more evolved than the footwall and hangingwall units. Furthermore, plagioclase showed reverse zoning in the anorthosite footwall unit while normal zoning was identified in the anorthosite reef unit. This suggested that the footwall unit underwent reheating and re-equilibration with a hotter, more primitive magma (also evident in recrystallization textures) while the anorthositic reef unit cooled relatively slowly and interstitial plagioclase present within this unit equilibrated with a trapped, more evolved liquid. The pyroxenite reef unit shows enrichment in incompatible elements and corresponding negative Eu anomalies, indicating the presence of trapped liquids. Cu, Ni and S concentrations remained low throughout the reef with the exception of a peak underlying the anorthositic seam and further enrichment underlying this peak. Platinum-group element geochemistry identified two major peaks: an upper peak which coincided with the peaks for Cu, Ni and S, and showed preferential enrichment in Pd and Au relative to other PGE, and a lower peak which coincided with the presence of chromitite and showed the preferential enrichment of Os, Ir, Ru, Rh and Pt relative to Pd, Au, Cu and Ni. The formation of the lower peak was consistent with a model involving the co-precipitation of chromite and PGE clusters (as PGM) while the upper peak was attributed to a model involving the collection of PGE by an immiscible sulphide liquid. Moreover, high Cu/Pd and Pt/Pd ratios in the lower pyroxenite unit indicated a process involving sulphide fractional segregation and scavenging while the inverse, present within the upper pyroxenite unit, suggested a more dynamic system involving the introduction of PGE-undepleted magma and S during simultaneous sulphide precipitation. Furthermore, a separation of PPGE peaks from IPGE peaks was observed within the pyroxenite unit, indicating a different partitioning behavior between PPGE and IPGE. The separation of these peaks is attributed to a sulphide liquid fractionation model while depletion haloes occurring in the proximity of the main PGE peaks was suggested to form through an Ostwald-ripening type mechanism. The results of this study are consistent with a model for the formation of the Merensky Reef involving a combination of geochemical processes, including sulphide segregation and fractionation, as well as multiple replenishments of magma.
Keywords: Uncatalogued